On Marginal Distributions under Progressive Type II Censoring: Similarity/Dissimilarity Properties - Amal Helu (12536797) (2017)
Currently, progressive censoring is intensively investigated by several researchers due to its ability to remove subjects from the experiment before the final termination point, thus saving time and cost. The closed form of marginal density of failure times under progressive type II censoring is essential to study the properties of statistical analysis under different censoring schemes. In this paper, we provide a different presentation of the marginal distribution under progressive type-II censoring and we derive closed forms for different special cases. In order to study the similarity/dissimilarity of marginal densities of order statistics for failure times, the overlap measure is used. We discovered that the overlap measure depends only on the effective size m. A numerical example based on a real life data regarding failure times of aircrafts' windshields is provided to quantify the amount of redundant information provided by the order statistics of the failure times under different progressive type-II schemes based on the overlap measure. Moreover, this data set is used as a pilot study to estimate the effective size m needed for future studies. Other Information Published in: Open Journal of Statistics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.4236/ojs.2017.74044